A systematic review of the importation theory as a contributor towards violence, misconduct and gang membership in correctional centres: a South African perspective: research - Fitz, Lincoln (Acta criminologica, 2018)
Institutional gangs, violence and inmate misconduct is a very prominent feature in correctional centres, to such an extent that they now pose a serious threat to the safety of the inmates, officials, and the broader community. According to researchers, the cause of the phenomena relates to the theories of deprivation and importation. The Deprivation Theory proposes that deviant behaviour is a product of the oppressive conditions that inmates are subjected to upon incarceration and the Importation Theory argues that individuals import their deviant characteristics to a correctional centre. This paper involves a systematic review of the importation theoretical concept from a South African perspective. The paper critically reviews the empirical literature on the Importation Theory that relates to inmate misconduct, violence and gang membership in correctional centres. The individual level variables identified by the Importation Theory include age, race/ethnicity, sociodemographic status, criminal history, gang affiliation, and substance abuse. The authors reviewed 23 studies, conducted between 2010 and 2017 that were predominantly from the United States and other countries. Studies of this nature were very limited in other countries including South Africa. The results indicate several general conclusions on certain variables, whereas in others, such as race, a different perspective was found within the South African context. Empirical evidence in the different variables was very limited, due to the non-existence of similar studies and the paper highlighted future research. The paper also presented the methodological limitation of the research.